Turkish Pre-Service Teachers' Experiences with Contemporary Technology Games and Perceptions About Teaching with Instructional Games - Ummugulsum Korkmaz; Zeynep Yurtseven Avci (Research in Social Sciences and Technology, 2016)
The present study investigates pre-service teachers' experience about playing technology games and their opinions about using contemporary technology to play games as an instructional tool. The participants are 272 pre-service teachers from a university in Middle Anatolia. The present study used mixed methods. The data was collected through an online survey that was created by the authors. The survey contains demographic questions about the participants` gender, major, whether they play technology games or not, and questions about which technology games they play, their opinions about using technology (IWBs and tablets) to play games for instruction, and for which instructional purposes they plan using technology to play games. Following research questions were investigated for the current study: 1. Whether pre-service teachers play technology games or not? If yes, which technology games they play? 2. Whether pre-service teachers plan to use interactive white boards and tablets that were distributed by the government under FATIH project to play technology games for educational purposes? 3. Whether pre-teachers' opinions about using the IWBs and tablets to play instructional games associated with their gender and playing technology games? 4. For which instructional purposes pre-service teachers plan to use IWBs and tablets to play instructional games? For the second and third questions descriptive statistics and crosstabs were conducted. For the first and fourth questions content analysis was applied. Fifty-four percent (n=148) of the pre-service teachers agreed to use the IWBs and tablets to play technology games for educational purposes while 46% (n=124) did not. There is no statistically significant association between gender and plans using the IWBs and tablets to play instructional games. There was a statistically significant association between who Playing Technology Games and Plans Using IWBs and Tablets to Play Instructional Games. Pre-service teachers who play technology games reported higher scores than the ones who do not play technology games. The participants suggested that using IWBs and tablets to play games would make learning fun and easy. The study has implications for teacher education and K-12 education policy. The present study also adds to the knowledge of whether the Y-generation pre-service teachers find the recent technology games useful for education or not.